Decellularized amniotic membrane Scaffolds improve differentiation of iPSCs to functional hepatocyte‐like cells. Issue 2 (28th August 2019) - Abazari, Mohammad Foad; Soleimanifar, Fatemeh; Enderami, Seyed Ehsan; Nasiri, Navid; Nejati, Fatemeh; Mousavi, Seyed Ahmad; Soleimani, Masoud; Kiani, Jafar; Ghoraeian, Pegah; Kehtari, Mousa
Abstract: Human‐induced pluripotent stem cells‐derived hepatocyte‐like cells (hiPSCs‐HLCs) holds considerable promise for future clinical personalized therapy of liver disease. However, the low engraftment of these cells in the damaged liver microenvironment is still an obstacle for potential application. In this study, we explored the effectiveness of decellularized amniotic membrane (dAM) matrices for culturing of iPSCs and promoting their differentiation into HLCs. The DNA content assay and histological evaluation indicated that cellular and nuclear residues were efficiently eliminated and the AM extracellular matrix component was maintained during decelluarization. DAM matrices were developed as three‐dimensional scaffolds and hiPSCs were seeded into these scaffolds in defined induction media. In dAM scaffolds, hiPSCs‐HLCs gradually took a typical shape of hepatocytes (polygonal morphology). HiPSCs‐HLCs that were cultured into dAM scaffolds showed a higher level of hepatic markers than those cultured in tissue culture plates (TCPs). Moreover, functional activities in term of albumin and urea synthesis and CYP3A activity were significantly higher in dAM scaffolds than TCPs over the same differentiation period. Thus, based on our results, dAM scaffold might have a considerable potential in liver tissue engineering, because it can improve hepatic differentiation of hiPSCs which exhibited higher level of the hepatic marker and more stable metabolic functions. Abstract : Liver tissue engineering as a therapeutic option for restoring of damaged liver function has a special focus on using native decellularized scaffolds. Decellularized amniotic membrane could provide a proper microenvironment that efficiently promotes hepatic differentiation of human‐induced pluripotent stem cells (hiPSCs).